African Breast Cancer—Disparities in Outcomes (ABC-DO): protocol of a multicountry mobile health prospective study of breast cancer survival in sub-Saharan Africa. Issue 8 (23rd August 2016) - McKenzie, Fiona; Zietsman, Annelle; Galukande, Moses; Anele, Angelica; Adisa, Charles; Cubasch, Herbert; Parham, Groesbeck; Anderson, Benjamin O; Abedi-Ardekani, Behnoush; Schuz, Joachim; dos Santos Silva, Isabel; McCormack, Valerie
Abstract : Introduction: Sub-Saharan African (SSA) women with breast cancer (BC) have low survival rates from this potentially treatable disease. An understanding of context-specific societal, health-systems and woman-level barriers to BC early detection, diagnosis and treatment are needed. Methods: The African Breast Cancer—Disparities in Outcomes (ABC-DO) is a prospective hospital-based study of overall survival, impact on quality of life (QOL) and delays along the journey to diagnosis and treatment of BC in SSA. ABC-DO is currently recruiting in Namibia, Nigeria, South Africa, Uganda and Zambia. Women aged 18 years or older who present at participating secondary and tertiary hospitals with a new clinical or histocytological diagnosis of primary BC are invited to participate. For consented women, tumour characteristics, specimen and treatment data are obtained. Over a 2-year enrolment period, we aim to recruit 2000 women who, in the first instance, will be followed for between 1 and 3 years. A face-to-face baseline interview obtains information on socioeconomic, cultural and demographic factors, QOL, health and BC attitudes/knowledge, and timing of all prediagnostic contacts with caregivers in orthodox health, traditional and spiritual systems. Responses are immediately captured on mobile devices that are fed into a tailored mobile health (mHealth) study management system. This system implements the study protocol, by prompting study researchers to phone women on her mobile phone every 3 months and, failing to reach her, prompts contact with her next-of-kin. At follow-up calls, women provide updated information on QOL, care received and disease impacts on family and working life; date of death is asked of her next-of-kin when relevant. Ethics and dissemination: The study was approved by ethics committees of all involved institutions. All participants provide written informed consent. The findings from the study will be published in peer-reviewed scientific journals, presented to funders and relevant local organisations and at scientific conferences.